Comparison of apoptotic cells between cryopreserved ejaculated sperm and epididymal sperm in stallions - Monteiro, Gabriel Augusto [UNESP]; Freitas-Dell'aqua, Camila de Paula [UNESP]; Guasti, Priscilla Nascimento [UNESP]; Dell'Aqua Júnior, José Antonio [UNESP]; Alvarenga, Marco Antonio [UNESP]; Landim, Fernanda da Cruz [UNESP]; Papa, Frederico Ozanam [UNESP] (Elsevier, 2012)
The development of a reliable technique to freeze epididymal semen would provide a unique opportunity to preserve valuable genetic material from unexpectedly lost stallions. The aim of this study was to compare the apoptotic indices of sperm obtained from ejaculate, sperm recently recovered from the epididymides (EP), and sperm recovered from epididymides stored at 5 C for 24 hours (EP-stored). For the first category, two ejaculates from seven stallions were collected and then submitted to cryopreservation using an egg yolk-based extender. One week after the last semen collection, the stallions were submitted to bilateral orchiectomy, and sperm from one of the cauda epididymis was harvested immediately after castration (EP). The remaining testicle was stored in a passive refrigeration container at 5 C for 24 hours before the cauda epididymal sperm was harvested (EP-stored). Sperm harvesting from the epididymis for EP and EP-stored was performed by retrograde flushing of the caudal portion of the epididymis using a skim milk-based extender. The recovered sperm was then cryopreserved using the egg yolk-based extender. Sperm motility parameters were studied by computerassisted semen analysis, and apoptosis was estimated by measuring caspase activity and membrane phospholipid translocation using epifluorescence microscopy. The samples were evaluated immediately (0 hour) and 8 hours after thawing. At 0 hour, no differences in sperm parameters were observed among the groups, but after 8 hours, significant statistical differences were observed in sperm motility parameters and plasma membrane integrity among the treatment groups. In addition, viable cells with no apoptotic signs were more prevalent in EP and EP-stored, suggesting that epididymal sperm is less sensitive to the cold shock caused by sperm cryopreservation.
Keywords: Epididymal; Sperm; Apoptosis; Cryopreservation